New database on procedures for publishing in agricultural journals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The International Potato Center (CIP) has developed a database on the procedures for publication in agricultural journals, listing the specific requirements of about 200 journaIs for writing and publication of scientific and technical articles. The...